2012
DOI: 10.1021/np300059n
|View full text |Cite
|
Sign up to set email alerts
|

Flacourtosides A–F, Phenolic Glycosides Isolated from Flacourtia ramontchi

Abstract: In an effort to identify novel inhibitors of chikungunya (CHIKV) and dengue (DENV) virus replication, a systematic study with 820 ethyl acetate extracts of madagascan plants was performed in a virus-cell-based assay for CHIKV, and a DENV NS5 RNA-dependent RNA polymerase (RdRp) assay. The extract obtained from the stem bark of Flacourtia ramontchi was selected for its significant activity in both assays. Six new phenolic glycosides, named flacourtosides A-F (1-6), phenolic glycosides itoside H, xylosmin, scoloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…Similarly, products extracted from the leaves of the Madagascan plant Anacolosa pervilleana, demonstrated moderate activity in vitro against CHIKV replication (Bourjot et al, 2012b;Bourjot et al, 2012c). More recently, Kaur et al (2013) identified amongst a highly purified natural product compound library, a cephalotaxine alkaloid called harringtonine that displayed potent inhibition of CHIKV infection affecting CHIKV RNA production as well as viral protein expression with minimal cytotoxicity.…”
Section: Interferonmentioning
confidence: 99%
“…Similarly, products extracted from the leaves of the Madagascan plant Anacolosa pervilleana, demonstrated moderate activity in vitro against CHIKV replication (Bourjot et al, 2012b;Bourjot et al, 2012c). More recently, Kaur et al (2013) identified amongst a highly purified natural product compound library, a cephalotaxine alkaloid called harringtonine that displayed potent inhibition of CHIKV infection affecting CHIKV RNA production as well as viral protein expression with minimal cytotoxicity.…”
Section: Interferonmentioning
confidence: 99%
“…Evaluation of the selective antiviral activity of (5) and (6) virus-cell-based assay for SFV and SINV did show some antiviral effect (data not shown), but no 100% inhibition of virus-induced CPE was observed as for CHIKV (for all three assays, the same Vero cell line was used). In a previous study we found that betulinic acid 3β-caffeate elicited a significant inhibitory effect on the replication of CHIKV but with some cytotoxic activity [23]. Recently, a series of oleanan-type triterpenoids including glycyrrhizin and its aglycone, glycyrrhetic acid, were shown to possess anti-herpes simplex virus type 1 (HSV-1) activity in vitro [24].…”
Section: Resultsmentioning
confidence: 99%
“…This is an important approach since inhibition of these enzymes can disrupt virus life cycle. Most of the studies herein described were conducted in vitro using enzymatic assays [8,[47][48][49][50][51][52] or viral strain/replicon on cells evaluating replication, inhibition and/or protein expression [49, 51-54, 56, 68-71. Three studies were conducted utilizing in silico docking approach [57,58,72].…”
Section: Discussionmentioning
confidence: 99%